2018
DOI: 10.1073/pnas.1719397115
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent computations for visual pattern completion

Abstract: SignificanceThe ability to complete patterns and interpret partial information is a central property of intelligence. Deep convolutional network architectures have proved successful in labeling whole objects in images and capturing the initial 150 ms of processing along the ventral visual cortex. This study shows that human object recognition abilities remain robust when only small amounts of information are available due to heavy occlusion, but the performance of bottom-up computational models is impaired und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
165
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(197 citation statements)
references
References 36 publications
13
165
1
Order By: Relevance
“…It has been shown that, electrophysiologically, the initial sweep of rapid visually selective signals along the ventral VC (VVC) is unaffected by backward masking 14 . Consistent with the idea that backward masking interrupts recurrent processing, recent work has shown that the introduction of a rapid mask interferes with the ability to perform visual recognition tasks that require more processing time such as pattern completion, 48 as elaborated in the section entitled “Generalization in visual recognition” (Fig. 3A and 3B).…”
Section: The Role Of Recurrence In Visual Recognitionmentioning
confidence: 95%
See 4 more Smart Citations
“…It has been shown that, electrophysiologically, the initial sweep of rapid visually selective signals along the ventral VC (VVC) is unaffected by backward masking 14 . Consistent with the idea that backward masking interrupts recurrent processing, recent work has shown that the introduction of a rapid mask interferes with the ability to perform visual recognition tasks that require more processing time such as pattern completion, 48 as elaborated in the section entitled “Generalization in visual recognition” (Fig. 3A and 3B).…”
Section: The Role Of Recurrence In Visual Recognitionmentioning
confidence: 95%
“…Modified from Ref. 48. (C) The fraction of neural response variance explained for neurons in macaque inferior temporal cortex.…”
Section: The Role Of Recurrence In Visual Recognitionmentioning
confidence: 99%
See 3 more Smart Citations